2021
DOI: 10.7717/peerj.10882
|View full text |Cite
|
Sign up to set email alerts
|

What are the limits on whale ear bone size? Non-isometric scaling of the cetacean bulla

Abstract: The history of cetaceans demonstrates dramatic macroevolutionary changes that have aided their transformation from terrestrial to obligate aquatic mammals. Their fossil record shows extensive anatomical modifications that facilitate life in a marine environment. To better understand the constraints on this transition, we examined the physical dimensions of the bony auditory complex, in relation to body size, for both living and extinct cetaceans. We compared the dimensions of the tympanic bulla, a conch-shaped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
(59 reference statements)
1
2
0
Order By: Relevance
“…We initially hypothesized that xenorophid dolphins had proportionally smaller tympanic bullae than archaeocete whales, and collected measurements of bulla length and bizygomatic width for archaeocetes, odontocetes, and mysticetes in order to explore the evolution of relative bullar size in Cetacea. The length of the tympanic bulla across Cetacea correlates well with body size, but within each subgroup (Archaeocetes, Toothed Mysticetes, Stem Odontocetes, Crown Odontocetes), the trend of the convex hull for each group is quite similar, but with a slightly shallower slope for Mysticeti (e.g., proportionally smaller bullae at larger body sizes), broadly concordant with the findings of Groves et al [180]. Further, large archaeocetes like Basilosaurus and physeteroids tend to have proportionally smaller bullae than close relatives with smaller body size.…”
Section: Evolution Of Bulla Size In Cetaceasupporting
confidence: 88%
“…We initially hypothesized that xenorophid dolphins had proportionally smaller tympanic bullae than archaeocete whales, and collected measurements of bulla length and bizygomatic width for archaeocetes, odontocetes, and mysticetes in order to explore the evolution of relative bullar size in Cetacea. The length of the tympanic bulla across Cetacea correlates well with body size, but within each subgroup (Archaeocetes, Toothed Mysticetes, Stem Odontocetes, Crown Odontocetes), the trend of the convex hull for each group is quite similar, but with a slightly shallower slope for Mysticeti (e.g., proportionally smaller bullae at larger body sizes), broadly concordant with the findings of Groves et al [180]. Further, large archaeocetes like Basilosaurus and physeteroids tend to have proportionally smaller bullae than close relatives with smaller body size.…”
Section: Evolution Of Bulla Size In Cetaceasupporting
confidence: 88%
“…As shown in previous studies of Cetacea (e.g. Groves et al, 2021; Lanzetti et al, 2022), skull allometry can vary significantly across taxa. Therefore, we first tested for differences in allometry among genera and obtained taxon-specific regression parameters.…”
Section: Methodsmentioning
confidence: 54%
“…In fact, the relationship between the morphology of components of the auditory apparatus, such as the middle ear ossicles, cochlea, and bony labyrinth, and ecology has been studied before in numerous species (Bhagat et al, 2020;Kerber & Sánchez-Villagra, 2018;Mason, 2001Mason, , 2016Mason et al, 2010;Pfaff et al, 2015;Pleštilová et al, 2021). Tympanic bullar morphology itself has been investigated in specific species of mammals (Basso et al, 2017;Groves et al, 2021;Koper et al, 2021), including rodents (Alhajeri et al, 2015;Momtazi et al, 2008;Pleštilová et al, 2021;Potapova, 2019;Schleich & Vassallo, 2003;Tabatabaei Yazdi et al, 2014;Zherebtsova & Potapova, 2019) and has been shown to be associated with habitat use. In particular, inflated tympanic bullae and the associated sound amplification have been linked to open and arid environments (Alhajeri et al, 2015;Tabatabaei Yazdi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%